2022
DOI: 10.1111/ejh.13769
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization trends in patients with acute myeloid leukemia ineligible for intensive chemotherapy receiving first‐line systemic treatment or best supportive care: A multicenter international study

Abstract: Objectives This retrospective chart review examined real‐world healthcare resource utilization (HRU) in patients with AML ineligible for intensive therapy who received first‐line systemic therapy or best supportive care (BSC). Methods Data were collected anonymously on patients with AML who initiated first‐line hypomethylating agents (HMA), low‐dose cytarabine (LDAC), other systemic therapy, or BSC. HRU endpoints included hospitalizations, outpatient consultations, transfusions, and supportive care. Results Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Here, we showed that colistin sulfate was less cytotoxic to leukemia cell lines than a normal kidney cell line. When Speranzini et al 14 treated MV-4-11 cells with colistin, they did not observe any significant alteration in cell growth or H3-Lys 4 /H3-Lys 9 methylation. However, this study used a relatively low concentration of colistin sulfate (1.2 µg/mL, 0.85 µM), given that our study found an IC 50 of this agent in the same cells to be 888 µg/mL (768.5 µM).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here, we showed that colistin sulfate was less cytotoxic to leukemia cell lines than a normal kidney cell line. When Speranzini et al 14 treated MV-4-11 cells with colistin, they did not observe any significant alteration in cell growth or H3-Lys 4 /H3-Lys 9 methylation. However, this study used a relatively low concentration of colistin sulfate (1.2 µg/mL, 0.85 µM), given that our study found an IC 50 of this agent in the same cells to be 888 µg/mL (768.5 µM).…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, infection, due to treatment-related immunosuppression, expression of immunosuppressive molecules or specific defects in the immune response, remains a major cause of death in patients with AML, requiring antibacterial or antiviral therapies to treat infections during first-line treatment. 4 Given the high costs, high risk of failure and protracted development times of new chemotherapy drugs, exploiting the off-target effects of existing antimicrobial agents is an attractive approach to improve survival rates in cancer p[atients.…”
Section: Introductionmentioning
confidence: 99%
“…The Real-World Treatment Patterns and Clinical Outcomes in Unfit AML Patients Receiving First Line Systemic Treatment or Best Supportive Care (CURRENT) study was a multicenter, multinational non-interventional retrospective chart review designed to understand the clinicopathologic characteristics, treatment patterns, clinical outcomes (including survival), and HRU of AML patients who are unfit to receive intensive chemotherapy in real-world clinical practice. Overall results of the global study have been published elsewhere [ 19 , 20 ]. The focus of this manuscript is the results for the Canadian dataset from the global study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ICU admission rate, supportive care needs (eg, transfusion, antimicrobials), and long-term complications, such as graft-versus-host disease in transplant recipients, have been shown in multiple studies to be associated with a substantial economic burden on the healthcare system. [27][28][29] Reducing the rate of complications can therefore be an important aspect not only from a patient's quality-of-life standpoint but also with regard to health economic considerations.…”
Section: Aml Care Costs Historic Perspective and Limitations Of Cost-...mentioning
confidence: 99%